2021
DOI: 10.1177/0042098020984908
|View full text |Cite
|
Sign up to set email alerts
|

Organising care and community in the era of the ‘gay disease’: Gay community responses to HIV/AIDS and the production of differentiated care geographies in Vancouver

Abstract: Scholarship on the place of the HIV/AIDS crisis in urban geographies of sexual minority activism has powerfully insisted on the importance of community organising as a response to state and societal failures and to their homophobic, AIDS phobic and morally conservative underpinnings. This paper extends this scholarship by examining the urban social geographies of exclusion produced by such community organising efforts. It draws on the perspectives of long-term survivors of HIV/AIDS (LTS) in Vancouver to highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Given that concealment of sexual identity is linked to poor mental health, it can reasonably also be assumed that it will be related to various aspects of sexual health. HIV/AIDS has often been referred to as a ‘gay disease’ (Catungal et al., 2021 ), indicating that sexual identity or sexual orientation has to do with the disease. However, HIV/AIDS is the result of individuals’ sexual behavior, and not of sexual identity or orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that concealment of sexual identity is linked to poor mental health, it can reasonably also be assumed that it will be related to various aspects of sexual health. HIV/AIDS has often been referred to as a ‘gay disease’ (Catungal et al., 2021 ), indicating that sexual identity or sexual orientation has to do with the disease. However, HIV/AIDS is the result of individuals’ sexual behavior, and not of sexual identity or orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, programs that address HIV-related stigma in healthcare settings should be holistic and include comprehensive knowledge about HIV, addressing the emotional and social factors that shape stigmatizing attitudes and practices. For example, previous studies have found that people associate HIV disease with being gay (Arscott et al, 2020; Catungal et al, 2021; Logie et al, 2020) and with activities considered to be immoral (Letamo, 2019; Seid & Ahmed, 2020). Thus, antistigma education is needed to address such beliefs and should include the historical aspects of HIV transmission, which indicate that no particular social group should be blamed or held morally responsible for spreading HIV.…”
Section: Discussionmentioning
confidence: 99%
“…An imagined topography of risk characterised the accounts of MSM in Denson et al's (2021) study of Black men in the US deep south. Imaginaries of treatment resources were said to characterise representations of the geographies of care among gay men in Vancouver, as shown by Catungal et al (2021), and Hassan and Tucker (2021) describe the construction of imagined communities around the risks faced by MSM in South Africa. The idea of imaginaries has been attractive because it permits a collective and politically nuanced account of how groups and individuals represent, discuss and act upon their social worlds and make topographies of risk, embodiment and community actionable.…”
Section: Introductionmentioning
confidence: 99%